Verbal fluency in vascular dementia – Clinical approach - Gliwa, Renata (Selected issues from the theory and practice of speech therapy, 2018)
The assumption of this study was the characterization of verbal fluency in vascular dementia. The verbal fluency test was used for the tests. The experimental group included 42 people. Quantitative and qualitative analysis of the research material was made. Problems with verbal fluency have been described: formal and categorial in patients with vascular dementia in the light, middle and deep degree.